2020
DOI: 10.1111/jcmm.15658
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of isoquercitrin on streptozotocin‐induced neurotoxicity

Abstract: Alzheimer's disease (AD) is characterized by irreversible and progressive memory loss and has no effective treatment. Recently, many small molecule nature products have been identified with neuroprotective functions and shown beneficial effects to AD patients. In the current study, we thus performed a small scale screening to determine the protective effects of natural compounds on streptozotocin (STZ)‐induced neurotoxicity and Alzheimer's disease (AD). We found that a lead flavonoid compound, isoquercitrin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…These abnormalities result in pathologies such as vasculopathies, neuropathies, ophthalmopathies, and nephropathies, among various other medical problems [ 10 ]. Through in vitro cell culture as well as in vivo diabetic rodent models for STZ-induced toxicity, it has been shown that STZ induces cellular oxidative stress and mitochondrial respiratory dysfunction [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These abnormalities result in pathologies such as vasculopathies, neuropathies, ophthalmopathies, and nephropathies, among various other medical problems [ 10 ]. Through in vitro cell culture as well as in vivo diabetic rodent models for STZ-induced toxicity, it has been shown that STZ induces cellular oxidative stress and mitochondrial respiratory dysfunction [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…IQC belongs to the bioflavonoid family and possesses pleiotropic biological effects under physiological and pathological conditions ( 13 , 28 , 29 ). Previous studies have shown that IQC has a neuroprotective effect by inhibiting neuronal apoptosis either in streptozotocin-induced neurotoxicity ( 30 ) or in cerebral ischemia/reperfusion injury ( 31 ). In addition to nerve cells, IQC has been proven to exert an anti-apoptotic effect in cardiomyocytes ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a meta-analysis of 17 preclinical studies on AD animal models revealed that EGCG exerts neuroprotective effects by reducing acetylcholinesterase activity, enhancing α-, β-, and γ-secretase activity, decreasing Aβ 42 levels and tau phosphorylation, and modulating anti-oxidative, antiinflammatory, and anti-apoptotic processes [146]. Moreover, the flavonoid isoquercitrin enhanced mitochondrial function by attenuating mitochondrial membrane potential loss, downregulating the outer mitochondrial membrane voltage-dependent anion channel (VDAC), and preventing mtROS accumulation in a model of streptozotocin-induced AD in murine Neuro-2a neuroblastoma cells [18]. Two other flavonoids, mangiferin, and morin, alleviated Aβ-induced mitochondrial impairments such as decreased respiratory capacity, mitochondrial membrane depolarization, and cytochrome c release in cortical neurons in the AD model [147].…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…In recent years, the beneficial health effects of flavonoids, naturally occurring polyphenolic compounds, have attracted medical research, including their utilization in pathologies associated with mitochondrial impairments [11] such as cancers, cardiovascular and neurodegenerative diseases [12]. The efficacy of flavonoids is supported by extensive preclinical evidence that represents the basis for further research into the potential future use of these compounds in specific targeted and personalized therapy of mitochondriopathies according to the 3PM approach [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%